δD values of biomarkers in Hala Hu sediment core H7 - Bernhard Aichner; Alice Callegaro; Marcel T J van der Meer; Bernd Wünnemann; Dada Yan; Yongzhan Zhang; Carlo Barbante; Dirk Sachse (PANGAEA, 2021)
Hydrogen isotope composition of aquatic (mid-chain n-alkenes, C20-HBIs, C37-alkenones) and terrestrial (long-chain n-alkanes) biomarker groups were analysed in core H7 from Hala Hu, China. The lake is located on the northern margin of the Tibetan Plateau (97.24 - 97.47°E, 38.12 - 38.25°N, 4078 m above sea level), along the modern marginal zone between the Asian Summer Monsoon (ASM) and westerlies influences. The core was drilled at the deepest point (65 m) of the lake and extends from 212 to 636 cm sediment depth. According to the age-model (Yan et al., 2020) the covered time period is 7462 - 23610 cal yr BP. After quantification of compounds, for separate δD-analysis of n-alkanes and n-alkenes, the non-polar aliphatic fraction was further split chromatographically into a saturated and unsaturated fraction, using aluminum-coated silicagel as stationary phase and hexane and DCM as solvents. To obtain sufficient amounts for isotope analysis, in some cases several samples have been merged, especially in the older section of the core. Compound specific hydrogen isotope values were then obtained by using gas chromatography isotope ratio mass spectrometry (GC-IRMS). We used a Thermo Scientific® Trace GC equipped with a Restek RTX-5 column (30 m, inner diameter 0.25 mm, film thickness 0.25 μm). The GC was connected via a GC Isolink with high temperature combustion furnace (1400 °C) and a Conflo IV interface to a Delta V Plus isotope ratio mass spectrometer. The δD values of the alkenones were determined by a GC/Thermal Conversion/isotope ratio monitoring mass spectrometer (GC-TC-irMS). For this a GC, equipped with a CPsil 5 CB column (250.167emmeters, 0.320.167emmm inner diameter, film thickness 0.40.167emμm) was coupled to a GC-isolink I via a Conflo IV to a Thermo Electron DELTA V mass spectrometer.
In: Aichner, B et al. (2021): Concentrations and δD values of biomarkers in sediment cores H7 and H11 from Hala Hu, China [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.933814